Juridical Analysis of the Village Head's Term of Office from a Constitutional Perspective - Hasan, Dahlan; B, Sumiyati; Marwan, Marwan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The Village Head has the position of village leader who is responsible for the prosperity and well-being of the village. The Village Head is an aspect that greatly influences the success or failure of developing a village. As the leader of the village government, the village head must be able to carry out his duties well and be able to regulate the performance of the village government to build a prosperous village and create a prosperous community. As a leader who is full of trust in managing and developing the village, the village head is assisted by village officials in handling all affairs in the village. The aim of this research is to determine the term of office of the village head from a constitutional perspective. This research uses normative legal research methods. Normative legal research is legal research carried out by examining library materials or secondary data. The revision of Law Number 6 of 2014 concerning Villages in Article 39 Paragraphs (1) and (2) which regulates terms of office and periodization is not the only way to maximize the performance of village heads, the government can make provisions for the requirements and quality of human resources. who will serve as village head because good human resources can change the quality and quantity of life of people in rural areas or cities.